Pengelolaan Program Vocational Skill dalam Meningkatkan Kompetensi Peserta Didik SKB Negeri Surabaya - Salma Adhwa Hanifah; Rofik Jalal Rosyanafi (J+PLUS UNESA, 2023)
The vocational skill program is one of the activities carried out at the Surabaya State SKB with the aim of increasing competence and exploring the potential of students through the skills provided. The increasing competence of Surabaya State SKB students is one of the backgrounds of this research. This research is a research with a descriptive qualitative approach. The research subjects were school principals, tutors and Surabaya State SKB students. Data collection was carried out in three ways, namely participatory observation, in-depth interviews and documentation. Data analysis techniques in this study are data condensation, data display and conclusions. The validity of this research data uses prolong engagement, triangulation of data sources, triangulation of data collection methods and member checks. The results of this study indicate that the management of vocational skill programs can improve students' competencies including cognitive competence, affective competence and pricomotor competence.